Enhanced Access to the CGIAR Virtual Library via Social Media - Ferreyra, Cecilia; Ramos, Mila; Álvare, Luz Marina (2010)
The Consultative Group on International Agricultural Research (CGIAR) has been very active in generating new agricultural knowledge through researches on diverse subjects undertaken by its fifteen agricultural research centers located in various parts of the world. The CGIAR Virtual Library (CGVLibrary), one of the major collaborative projects among information managers (IMs) in the system, aims at bridging the gap between agricultural research outputs and potential users. Since its launch in 2006, it has served as a key online gateway to global agricultural knowledge. Instant access is enabled to researches on agriculture, hunger, poverty, and the environment, especially the full text global public goods generated by the various centers in the CGIAR. While content development, quick retrieval, and improvement of web site interface are major concerns for the IMs, various avenues are being pursued to market the tool to prospective users. In the past, live seminars, paper presentations in conferences, publications in various venues, use of print media (flyers, posters, etc.) were utilized to link the CGV Library to worldwide researchers. The advent of social media altered the mode of information delivery to a large extent. In addition to conventional media, social networking tools are now being explored and utilized to market the CGV Library. This poster will show how social networking tools, such as Skype, Twitter, wikis, blogs, etc. are helping to create better awareness of the virtual library and to reach out to scientists in a more effective manner.